2021
DOI: 10.1002/ieam.4435
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air pollution and COVID‐19 severity: A review of current insights, management, and challenges

Abstract: Data availability statement:The data that support the findings of this study are available in the published literature also cited in the present manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Approximately 140,000 total deaths per year were attributable to total outdoor air pollution exposure in the U.S. from 2000 to 2010 ( Lelieveld et al 2015 ). There is evidence for both short and long-term exposure of air pollution to increase SARS-CoV-2 infections (transmission) as well as COVID-19 severity and mortality ( Ali et al 2021 ; Woodby, Arnold, and Valacchi 2021 ). Chronic exposure to air pollution results in increases in all-cause, cardiovascular, and influenza mortality ( Jiang, Mei, and Feng 2016 ; Pope et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 140,000 total deaths per year were attributable to total outdoor air pollution exposure in the U.S. from 2000 to 2010 ( Lelieveld et al 2015 ). There is evidence for both short and long-term exposure of air pollution to increase SARS-CoV-2 infections (transmission) as well as COVID-19 severity and mortality ( Ali et al 2021 ; Woodby, Arnold, and Valacchi 2021 ). Chronic exposure to air pollution results in increases in all-cause, cardiovascular, and influenza mortality ( Jiang, Mei, and Feng 2016 ; Pope et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to point out that the effect of exposure to air pollutants on COVID‐19 outcomes varied within regions. Several factors can explain the divergences, such as differences in lockdown policies and strategies, socioeconomic indicators, quality of healthcare services, geographical location, and meteorological parameters (Ali et al, 2021 ). For instance, a comparative study among China, England, Germany, and Japan indicated that the population density and absolute humidity influence both the SARS-COV-2 spread and the decay duration of the pandemic (Diao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Vaccinations reduce the population’s susceptible fraction [ 16 ]. Air pollution may enhance COVID-19 severity [ 17 ]. …”
Section: Methodsmentioning
confidence: 99%